PERAN LABORATORIUM DALAM INVENTARISASI CERITA SEJARAH KOTA DI KALIMANTAN BARAT - Utami, Nunik Esti; Syaifulloh, Muhammad (Universitas Muria Kudus, 2023)
The aim of this research is to determine (1) the variety of collections owned by the IKIP PGRI Pontianak history laboratory related to the inventory of city history stories in West Kalimantan, and (2) the role of the history laboratory in the inventory of city history stories in West Kalimantan, (3) student activities in the History education study program laboratory.The research method used is a qualitative method with a fixed case study strategy. The research was conducted at the History Education Laboratory of IKIP PGRI Pontianak and the West Kalimantan region. The data sources in this research are student informants and resource persons who can provide information about the history of the cities of West Kalimantan and the role of the history laboratory in inventorying the history of the city of West Kalimantan, the location of cities in West Kalimantan, documents in the form of letters, archives , photos or recordings.The collection techniques used in the research were direct observation, in-depth interviews, reviewing documents and archives (content analysis) regarding the role of history laboratories in inventorying the history of the city of West Kalimantan. Data validity uses source triangulation and method triangulation.The results of the research show that the IKIP PGRI Pontianak History Laboratory hasthree rooms, namely the Spatium Historica Didactica as an office administration room, the Agus Sastrawan Noor Spatium as a discussion and creation room, and the Sudarto Spatium as a West Kalimantan local history room which is used in collecting an inventory of the city's history. The role of the history laboratory in inventorying the city's historical stories is as a center for collecting and storing scientific historical information, and maintaining the accuracy and authenticity of historical stories and providing a deeper understanding of the history of the city and its people.